Occupational Health Hazards of Brass Worker in a selected community. - Jayawardana, P.L (My University, 1994)
Objective of this study was to determine the health problems and the associated risk factors of brass workers in the district of Kandy in comparison to a control group. Certain acute and chronic symptoms, metal fume fever, and accidents were significantly more among the brass workers than among the control, protective measures were used by less than 20 per cent of the brass workers. There was no difference in the clinical abnormalities and eye defects. The mean haemoglobin levels were almost similar, in the two groups while none had basophilic stippling. Health education programmes are necessary to improve the knowledge on occupational health hazards. It requests of the brass workers to the authorities, to provide effective protective gear at a low cost.